IDENTITAS GENDER DAN SEKSUAL SEBAGAI PERSONAL BRANDING PADA KONTEN TIKTOK LUCINTA LUNA - Joan Natasya Lambe; Vega Ulfie Rahmawati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
In this technological era, media plays an important role in building personal branding. Not only companies, but individuals also need strong personal branding to get people's attention. Lucinta Luna is one of the celebrities who use their gender and sexual identity to make content called "Khodam". It is interesting to study the use of gender and sexual identity as personal branding. The purpose of this study was to analyze the use of gender and sexual identity by Lucinta Luna after being released from prison. This study uses a qualitative descriptive approach with data collection techniques derived from 25 TikTok video content with the topic of "Khodam" which is Lucinta Luna's personal branding strength. Secondary data is obtained from documentation of collaborative content with other public figures and conventional media. The data were analyzed with eight concepts from Peter Montoya in building personal branding. The results of this study indicate that Lucinta Luna performs these eight concepts by prioritizing "Khodam" or a male voice that sometimes appears as a way to attract netizens' attention. Now Lucinta's image is considered more self-accepting, fun, and full of positive things